Transition‐Metal‐Free Radical Cyclization of 2‐Arylbenzoimidazoles with Unactivated Alkanes via C(sp3)−H Functionalizations in Aqueous Media. Issue 12 (17th May 2022) - Li, Jiao‐Zhe; Mei, Lan; Cai, Xue‐Er; Zhang, Can‐Can; Cao, Ting‐Ting; Huang, Xun‐Jie; Liu, Yi‐Lin; Wei, Wen‐Ting
Abstract: Here we present a transition‐metal‐free radical cyclization of 2‐arylbenzoimidazoles with unactivated alkanes. By using di‐ tert ‐butyl peroxide (DTBP) to promote the C( sp 3 )−H bond functionalization, this approach enables assembly of various benzimidazo[2, 1‐ a ]isoquinolin‐6(5 H )‐ones in aqueous media. This strategy can not only well tolerate a wide range of cyclic alkanes, straight‐chain alkanes, toluene derivatives, as well as pharmaceutical molecule eudesmol, but also provides an approach for the functionalization of unactivated C( sp 3 )−H bonds in aqueous media under transition‐metal‐free systems. Abstract :